2005
DOI: 10.1158/0008-5472.can-05-0513
|View full text |Cite
|
Sign up to set email alerts
|

Selective Inhibition of Ras, Phosphoinositide 3 Kinase, and Akt Isoforms Increases the Radiosensitivity of Human Carcinoma Cell Lines

Abstract: Ras activation promotes the survival of tumor cells after DNA damage. To reverse this survival advantage, Ras signaling has been targeted for inhibition. Other contributors to Ras-mediated DNA damage survival have been identified using pharmacologic inhibition of signaling, but this approach is limited by the specificity of the inhibitors used and their toxicity. To better define components of Ras signaling that could be inhibited in a clinical setting, RNA interference was used to selectively block expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
137
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(149 citation statements)
references
References 55 publications
(68 reference statements)
10
137
0
1
Order By: Relevance
“…For transient transfection, the siRNAs against the sequence 5 0 -AAGGAGGG UUGGCUGCACAAA-3 0 of the human Akt1 mRNA (Kim et al, 2005), the sequence 5 0 -GATGC CATTGAGGAATTAG-3 0 of the human Mre11 mRNA (Pichierri and Rosselli, 2004), and the sequence 5 0 -AAACUG CUAAAUGACGAGGAC-3 0 of the human b-catenin mRNA (Hadjihannas et al, 2006) were synthesized by GenChem Corporation (Shanghai, China). Lef-1 siRNA (h) was obtained from Santa Cruz Biotechnology (sc-35804).…”
Section: Constructs Retroviral Infection and Transfectionmentioning
confidence: 99%
See 1 more Smart Citation
“…For transient transfection, the siRNAs against the sequence 5 0 -AAGGAGGG UUGGCUGCACAAA-3 0 of the human Akt1 mRNA (Kim et al, 2005), the sequence 5 0 -GATGC CATTGAGGAATTAG-3 0 of the human Mre11 mRNA (Pichierri and Rosselli, 2004), and the sequence 5 0 -AAACUG CUAAAUGACGAGGAC-3 0 of the human b-catenin mRNA (Hadjihannas et al, 2006) were synthesized by GenChem Corporation (Shanghai, China). Lef-1 siRNA (h) was obtained from Santa Cruz Biotechnology (sc-35804).…”
Section: Constructs Retroviral Infection and Transfectionmentioning
confidence: 99%
“…Inhibition of phosphoinositide 3-kinase/Akt pathway leads to radiosensitization, such as glioblastomas, carcinoma of the breast, colon, bladder, prostate, head and neck and cervix (Gupta et al, 2002;Li et al, 2004;Altomare and Testa, 2005;Kim et al, 2005;Lee et al, 2006;Kao et al, 2007). One of the important reason is that activated Akt promotes survival of cells exposed to IR through inhibition of apoptosis (Brognard et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…In this context, Kim et al (45) reported that Ras signaling to PI3K-AKT is an important contributor to cell survival independent of whether it results from mutation of RAS or overexpression of EGFR. Furthermore, recently, we have reported that targeting of EGFR-PI3K signaling by specific small-molecule inhibitors (i.e., BIBX1382BS and LY294002) impairs repair of radiationinduced DNA double-strand breaks (mainly through the nonhomologous end-joining mechanism), resulting in enhanced radiosensitivity selectively of those human tumor cells that present mutated K-RAS gene (30,31).…”
Section: Introductionmentioning
confidence: 99%
“…Radiation survival curves were plotted after normalizing for the cytotoxicity induced by drug treatment alone. Linearquadratic curve equations were used to fit the SF curves shown in the figures using [12]. Oxygen enhancement ratios (OER) were calculated by dividing the D 10 value under hypoxia by the D 10 value under normoxic conditions.…”
Section: Clonogenic Assaymentioning
confidence: 99%